Systematic sustainability assessment (SSA) for conceptual design phase in Malaysia automotive industry - Turan, Faiz Mohd
Numerous companies are accepting sustainability as an organizational peremptory. There is, however, little convergence on how organizations become sustainable. The previous study suggests that a paradigm shift is necessary to incorporate more sustainable ways of thinking, while others advocate that sustainability requires only moderate behavioural changes as in attitude. In addition, it is also suggesting that sustainability develops most effectively when a singular view of sustainability is applied throughout the company; others contend that differentiated views of sustainability emerge within the various subcultures of an organization. The aim of this research is to analyse the aftermath of considering attitudinal parameter into the initial data, portraying the true nature of personality during the survey. The research presented was carried out with employees from automotive-related manufacturing companies with different branches of knowledge and attitude. Survey methodology was employed by building a questionnaire combining Likert-type items, Sustainable Development Goals (SDGs), Green Project Management (GPM) P5 Integration and multiple-option items. The results allow identifying the knowledge and attitudes of the employees of automotive-related company in Malaysia context, contributing relevant data in regard to future engagement relating to sustainability and attitudinal parameter.